Communicating about plant breeding and genome editing in plants: Assessment of European stakeholders, sources, channels and content. Issue 1 (16th August 2022) - Will, Sabine; Vangheluwe, Nick; Krause, Dörthe; Fischer, Arnout R. H.; Jorasch, Petra; Kohl, Christian; Nair, Abhishek; Nanda, Amrit K.; Wilhelm, Ralf
Abstract: Genome editing helps to develop plant varieties that address future agricultural challenges such as climate change adaptation, resource efficiency and sustainable productivity. Nevertheless, associated aspects relating, besides others, to the regulation of genome editing, intellectual property rights and potential environmental and health aspects lead to fierce discussions within the European Union. In these discussions, values and moral aspects play a decisive role. To support and set the stage for an open‐minded dialogue, the communication behaviour and needs of specific stakeholder groups has been analysed by means of two online surveys. The surveys considered sources and channels used for information sourcing and dissemination, conveyed content and relevant target audiences. In addition, the degree of trust of stakeholders in different information sources was assessed. Stakeholders included representatives from academia, civil society organisations (including environmental and consumer organisations), journalists, the farming community, the seed and plant breeding sector and policymakers across Europe. Our analysis suggests that, in general, a high level of trust is associated with representatives from academia, and that safety‐related aspects, transparency and sustainability are considered very important topics across the different stakeholder groups. In addition, social media seem to play a subordinate role for inter‐stakeholder communication but is of higher relevance for reaching out to the public. Abstract : To facilitate an open‐minded dialogue on plant genome editing, the communication behaviour of key actors has been analysed. The analysis included sources and channels used for information sourcing and dissemination, conveyed content, relevant target audiences and the degree of trust stakeholders put into the different actors. From the provided data, five recommendations are derived that should inform the communication about plant genome editing in the future